Aukusti Robert Niemi and His Collection of Folklore from Southern Lithuania Revisited. Textological Approach - Daugirdaitė, Vilma (Tautosakos darbai, 2018)
The Lithuanian folklore collections by the Finnish folklorist Aukusti Robert Niemi seem symbolically to enframe his two decades of the Lithuanian cultural activity. Professor started from doing fieldwork (visiting northeastern Lithuania in 1910 and southern Lithuania in 1911), which subsequently formed the basis for his scholarly research. In 1931, just before Niemi died, the manuscripts of his folklore collections returned to Lithuania from Finland in order to get the fieldwork materials of 1911 finally edited and published. The two decades in-between served to form and establish in the Lithuanian historiography the pattern of particularly positive appreciation of professor’s Lithuanian activities, the basis for which was the collection produced as result of his fieldwork in 1910, entitled “Lithuanian Songs and Chants in the Northeastern Lithuania” and published in 1912.This article aims at revising the established mode of evaluating the Lithuanian traditional folklore collected by Niemi. The subject of analysis consists of the manuscript collection of the southern Lithuanian folklore, which, although edited for publication, remained nevertheless unpublished. This collection consists of two separate archived folders preserved at the Lithuanian Folklore Archives of the Institute of Lithuanian Literature and Folklore. It has been endowed status of a trustworthy source in the historiography of Lithuanian folklore research and the source editing tradition, without proper consideration of possible complications caused by the shape of this collection, the linguistic problems encountered by a foreign researcher recording oral folksongs, and the geographic area of recording, which significantly exceeded the boundaries of southern Lithuania.The manuscript folklore collection from southern Lithuania is peculiar in terms of one mode of evaluation required by the fieldwork notes and quite another – by the copy of the manuscript, which allows for reconstructing the collection as a whole, since part of the original autograph is lost. In the course of analysis, the texts from the copy and those from the autograph were thoroughly compared. This comparison highlighted certain changes having taken place in the copy, which perhaps resulted from carelessness, inexperience or neglect by the copyists or editors readying the texts for publication, as well as from specific problems inherent in the autograph and causing reasonable doubt in the trustworthiness of the copy. In the process of archiving, there occurred a mistake resulting in a sheaf of miscellaneous folklore from various places in Lithuania being added to the original collection. These texts subsequently found their way into the card file catalogues of Lithuanian riddles, proverbs and folksongs as authentic recordings; although according to the catalogues, they should have been regarded as copies from the folklore collections by the Lithuanian Science Society. So far, the fieldwork notes by Niemi were usually thought to have been produced by his assistants, who actually recorded the texts. The textological analysis of fieldwork notes from southern Lithuania enabled revision of such assumptions. Although Niemi’s assistants did lend him a hand in recording the folksong texts, certain peculiarities of the recordings allow us assuming that the majority of the material was noted down by the professor himself, who did not know the Lithuanian language sufficiently. This would clarify numerous inaccuracies that impede reading and understanding of the autograph: confused vowels and consonants, distorted words and lexical forms (these seem to be acoustic lapses resulting in random joining of separate syllables into words without considering the actual meaning of the text), as well as incoherent and fragmented character of the texts. However, unbiased appreciation of the folkloric legacy by the Finnish researcher Niemi is only possible with due consideration of the textological problems and quality issues inherent in his texts. Besides, sufficient elucidation of the circumstances under which this collection was compiled and the scholarly intentions of its collector could add attractiveness to it, particularly if the subtle textological nuances can be made relevant as peculiar marks left by a foreign speaking collector.
Keywords: -